Ukraine as a Geopolitical Priority of the Russian Federation - Kondratenko, Oleg (Historia i Polityka, 2016)
The article determines the meaning of confrontation between the leading centers of international pressure. According to the geographical status, Ukraine can be the main confrontation object between the USA, Russia, and the EU in order to show their presence in the Eurasian region. Nowadays Ukraine is considered to be one of the key countries that can transform the world order.